Exploring early childhood development programming in Kenya’s arid and semi-arid lands - Phyllis Magoma; Amina Abubakar; Martha Kaniala; Barack Aoko; Moses Esala; Joyce Marangu; Susan Nyamanya; Margaret Kabue; Siad Guyo; Abubakar Baasba; John Ng'asike; Anil Khamis; et al. (South African Journal of Childhood Education)
Background: Promoting high-quality early childhood development (ECD) is vital for individuals’ physical and social well-being and yields significant societal returns. However, children in marginalised regions like Kenya’s arid and semi-arid lands (ASALs) face significant barriers to accessing quality ECD services.